JC's total body transformation the very best workouts for strength, fitness, and function - Santana, Juan Carlos 1959- (Human Kinetics, 2019)
"JC's Total Body Transformation provides more than 100 workouts, each professionally designed, proven effective, and ready to use. The book also gives nutritional tips that will get you to your goal faster than you ever thought possible. Renowned for his functional training approach, he has designed countless workouts and knows how to deliver results. With JC's Total Body Transformation, you'll have access to all of this: 107 ready-to-use workouts for athletic performance, strength, mobility, and transformation; tips on using multiple pieces of equipment--including barbells, dumbbells, and medicine balls--to target different muscles and add variety; nutrition tips to help torch fat and build muscle; advice on rest and recovery; examples from JC's clients about how specific workouts delivered the results they wanted; bonus workouts from industry giants in athletic performance, bodybuilding, and physique competition. The best part is that you can use these workouts on their own or incorporate them into your existing training plans. These workouts take into account the unique needs of men and women and provide modifications for different types of equipment and guidance on how to sequence workouts to create daily, monthly, and yearly programs."